2011
DOI: 10.1051/0004-6361/201015537
|View full text |Cite
|
Sign up to set email alerts
|

Optical atmospheric extinction over Cerro Paranal

Abstract: Aims. The present study was conducted to determine the optical extinction curve for Cerro Paranal under typical clear-sky observing conditions, with the purpose of providing the community with a function to be used to correct the observed spectra, with an accuracy of 0.01 mag airmass −1 . Additionally, this work was meant to analyze the variability of the various components, to derive the main atmospheric parameters, and to set a term of reference for future studies, especially in view of the construction of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 41 publications
(76 reference statements)
5
130
0
Order By: Relevance
“…Fig. 21), we found that both quantities were highly correlated, reinforcing the findings of Patat et al (2011) and validating our water telluric correction approach. Furthermore, using an orthogonal distance regression we find a saturation exponent of ρ = 0.62 ± 0.01 from the best power law describing the distribution (cf.…”
Section: Aerosol Comparisonsupporting
confidence: 87%
See 2 more Smart Citations
“…Fig. 21), we found that both quantities were highly correlated, reinforcing the findings of Patat et al (2011) and validating our water telluric correction approach. Furthermore, using an orthogonal distance regression we find a saturation exponent of ρ = 0.62 ± 0.01 from the best power law describing the distribution (cf.…”
Section: Aerosol Comparisonsupporting
confidence: 87%
“…Nevertheless, we do expect to have more stable values since the measurements are made at night far above the inversion layer, and the mean optical depth value is compatible with aerosols from maritime origins. Patat et al (2011) showed that the water band equivalent width at 7200 Å is well correlated with the Preciptable Water Vapor (PWV) at the Paranal site in Chile. In order to check the consistency of our approach, we compare our water intensity measurement to the PWV amount at Mauna Kea.…”
Section: Aerosol Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…During this study, we identified a systematic difference between our flux calculations for Jupiter and the corresponding magnitude value provided by widely available astronomy software (Downey, 2015) using the formula (Thuillier et al, 2003), albedo of Jupiter (Karkoschka, 1998), and atmospheric extinction at Cerro Paranal (Patat et al, 2011). Column 5 is the product of solar irradiance at 1 AU and Jupiter albedo (defined as B(λ) in Eq.17) with units of watts per meter squared per nanometer.…”
Section: Astronomical Sourcesmentioning
confidence: 99%
“…For this study, we use values from Patat et al (2011) to provide a lower bound on extinction effects. The upper bound is estimated using an empirical model based on Vargas et al (2002) and Zhang et al (2013).…”
Section: Atmospheric Effectsmentioning
confidence: 99%